Sales development as a market entry strategy for B2B firms - Yrjänen, Meri (My University, 2021)
Sales development is gaining a lot of interest among practitioners, yet the academic understanding of the function is scarce. There is a clear research gap about the changing sales force structures and about sales development for instance, and researchers request to shed light on the subject. The purpose of this study is to understand how sales development could be used as a facilitator of international market entry in the business-to-business market. The main research problem is divided into three sub-questions: what sales development is and how to organize sales development function that creates value and revenue for business-to-business companies, what are the requirements for integrated multifunctional sales funnel management, and what are the strategic and operational benefits and costs of utilizing sales development in the B2B international market entry context. This study consists of a literature review as well as an empirical study, conducted as qualitative research, utilizing an abductive process. Semi-structured theme interviews were conducted with nine individuals representing eight companies. The findings of this thesis align with the academic literature but also extend the understanding and provide more fine-grained information about sales development. The understanding of sales development was broadened: sales development is a function between sales and marketing, having the objective of lead qualification and nurturing and the tasks of sales development can be divided into inbound, outbound, and account-based functions. Findings indicate that sales development could facilitate international market entry through four business processes: market sensing, market experimentation, coordination of functions, and extension of resources. Also, the requirements for integrated multifunctional sales funnel management were identified: jointly defined processes, a culture of open communication, transparency in data, and shared targets. To conclude, this thesis contributes to the theory and management literature by producing a novel understanding of the function and being the first one to provide a framework to enable the structured understanding of the roles, tasks, and processes of sales development as well as its connections with internationalization strategies and sales-marketing integration.
Keywords: sales development, sales force specialization, lean internationalization, B2B